2009
DOI: 10.1002/stem.191
|View full text |Cite
|
Sign up to set email alerts
|

Stem-Like Ovarian Cancer Cells Can Serve as Tumor Vascular Progenitors

Abstract: Neovascularization is required for solid tumor maintenance, progression, and metastasis. The most described contribution of cancer cells in tumor neovascularization is the secretion of factors, which attract various cell types to establish a microenvironment that promotes blood vessel formation. The cancer stem cell hypothesis suggests that tumors are composed of cells that may share the differentiation capacity of normal stem cells. Similar to normal stem cells, cancer stem cells (CSCs) have the capacity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 27 publications
4
140
0
1
Order By: Relevance
“…The same group has demonstrated that breast cancer stem/progenitor cells are capable of differentiating into TECs [9]. Likewise, Alvero et al [57] have shown that TECs may originate from a subset of ovarian cancer cells with a highly angiogenic phenotype and the features of cancer stem cells. The connection between neural stem cells and the endothelial compartment seems to be critical in glioblastoma, where cancer stem cells closely interact with the vascular niche and promote angiogenesis [58].…”
Section: Discussionmentioning
confidence: 96%
“…The same group has demonstrated that breast cancer stem/progenitor cells are capable of differentiating into TECs [9]. Likewise, Alvero et al [57] have shown that TECs may originate from a subset of ovarian cancer cells with a highly angiogenic phenotype and the features of cancer stem cells. The connection between neural stem cells and the endothelial compartment seems to be critical in glioblastoma, where cancer stem cells closely interact with the vascular niche and promote angiogenesis [58].…”
Section: Discussionmentioning
confidence: 96%
“…CD44 + type I epithelial ovarian cancer cells have been demonstrated to form vascular structures when cultured in Matrigel conditions in vitro and to transdifferentiate into CD34 + endothelial progenitor cells (35). The progeny of glioma CSCs cultured in endothelial conditions have previously exhibited features of functional endothelial cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…These patient samples were obtained from patients at Yale New Haven Hospital (New Haven, CT) who were diagnosed with stage III/IV serous ovarian cancer and propagated as described previously (9,10,14,(28)(29)(30)(31)(32)(33) …”
Section: Methodsmentioning
confidence: 99%